Estimation of Growth Rates of Escherichia coli BJ4 in Streptomycin-Treated and Previously Germfree Mice by In Situ rRNA Hybridization - Rang, Camilla U. (American Society for Microbiology, 1999)
The growth physiology of Escherichia coli during colonization of the intestinal tract was studied with four animal models: the streptomycin-treated mouse carrying a reduced microflora, the monoassociated mouse with no other microflora than the introduced strain, the conventionalized streptomycin-treated mouse, and the conventionalized monoassociated mouse harboring a full microflora. A 23S rRNA fluorescent oligonucleotide probe was used for hybridization to whole E. coli cells fixed directly after being taken from the animals, and the respective growth rates of E. coli BJ4 in the four animal models were estimated by correlating the cellular concentrations of ribosomes with the growth rate of the strain. The growth rates thus estimated from the ribosomal content of E. coli BJ4 in vivo did not differ in the streptomycin-treated and the monoassociated mice. After conventionalization there was a slight decrease of the bacterial growth rates in both animal models.